Evaluation of clinical pathway implementation and clinical practice guidelines in the management of deep neck abscess (DNA) at Dr. Sardjito, General Hospital Yogyakarta, Indonesia - Dian Paramita Wulandari; Hesti Dyah Palupi; Feri Trihandoko (Universitas Gadjah Mada, 2022)
Deep neck abscess (DNA) is an infectious condition categorized as anemergency case with high mortality and morbidity. The incidence decreasesover time due to extensive use of antibiotics, operative intervention, andimproved awareness of dental hygiene. Management of DNA must be carriedout appropriately and efficiently to prevent complications that may occur,such as jugular vein thrombosis, pericarditis, and pneumonia. Patients withDNA are often categorized as high-cost patients, because of the long durationof hospitalization, the need for special examinations, and complicatedmanagement. Clinical practice guidelines (CPG) and clinical pathways (CP)are a standard created for management, quality, and cost control. The studyaimed to evaluate the implementation of the CPG and CP in DNA patients atDr. Sardjito General Hospital, Yogyakarta. The study used medical recordsdata of DNA patients from January 2018 to December 2020 who met theinclusion and exclusion criteria. A total of 55 subjects were obtained, withcompliance to complete CPG filling of 98.3% and CP filling of 96.2%. There was100% completion in CPG filling categorized as good compliance, whilst thenumber of good compliances for CP was 92.7%. In conclusion, the diagnosisand management of DNA patients at Dr. Sardjito General Hospital has goodcompliance with CPG and CP available.